Evaluation of Corrosion Behavior by Measuring Passivation Current Density of Dental Implant Coated with Bioceramic Materials. - Hameed, Hanan Ali; Hasan, Haider Ali; Alam, Mohammad Khursheed (BioMed Research International, 2021)
Background. This paper reports the corrosion behavior of uncoated commercially pure titanium and Ti-6Al-4V samples and these coated with hydroxyapatite, partial stabilized zirconia (PSZ), and the mixture of partial stabilized zirconia and hydroxyl-apatite by measuring passivation current density and see if there are any differences between them using electrochemical polarization tests in 37°C Hank's solution. Materials and Methods. The electrophoretic deposition method (EPD) was elected to keep the coating materials which are HA, PSZ, and the mixture of 50% HA and 50% PSZ on Cp Ti and Ti-6Al-4V alloy samples. The electrochemical corrosion test was achieved by exposing the coated and uncoated samples to Hank's solution which prepared in the laboratory and measuring the polarization potential, passivation current density, and the open circuit potential for all samples. Results. The results indicated that the passivation current density for all Cp Ti and Ti-6Al-4V alloy groups that coated with HA, PSZ, and with mixture of 50/50 HA and PSZ was less than uncoated groups. There are no significant differences between all Cp Ti groups when compared with all Ti-6Al-4 V alloy groups. The open circuit potential (OCP) for both Cp Ti and Ti -6Al -4V samples was in the following sequence PSZ > HA > mixture of HA and PSZ > uncoated. Conclusions. Coating significantly decreased the passivation current density of Cp Ti and Ti-6Al-4V alloy.